Postpartum Hemorrhage Management, Risks, and Maternal Outcomes: Findings From the World Health Organization Multicountry Survey on Maternal and Newborn Health. Issue 1 (March 2015) - Sheldon, W.R.; Blum, J.; Vogel, J.P.; Souza, J.P.; Gülmezoglu, A.M.; Winikoff, B.
Abstract : ( BJOG . 2014;121(suppl 1):5–13)